2011
DOI: 10.5194/aab-54-107-2011
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchange in selected horse breeds (<i>Equus caballus</i>)

Abstract: In studies of chromosome instability, the sister chromatid exchange (SCE) test is a particularly sensitive cytogenetic assay for detecting DNA damage. SCE tests of chromosome instability were performed in the group of 6 horse breeds (Pure-bred Arabian, Malapolski horse, Polish noble half-bred, Polish cold-blooded, Hucul and Polish Konik). The chromosome preparations were obtained from our in vitro culture of peripheral blood lymphocytes stained using the FPG technique. The mean number of SCEs/cell in the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
3
17
1
Order By: Relevance
“…Few publications contain reports about statistically significant differences in SCE incidence between males and females (Margolin and Shelby 1985;Husum et al 2008;Szeleszczuk et al 2014). Comprehensive studies of farm animals have not confirmed the effect of the sex on SCE frequency (Iannuzzi et al 1991b;Di Meo et al 1993, 2000Ciotola et al 2005;Peretti et al 2006;Wo´jcik et al 2011Wo´jcik et al , 2013Wo´jcik et al , 2014Wo´jcik and Smalec 2012a). The present authors also did not observe significant differences in the mean number of SCEs between chinchillas of different sexes.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Few publications contain reports about statistically significant differences in SCE incidence between males and females (Margolin and Shelby 1985;Husum et al 2008;Szeleszczuk et al 2014). Comprehensive studies of farm animals have not confirmed the effect of the sex on SCE frequency (Iannuzzi et al 1991b;Di Meo et al 1993, 2000Ciotola et al 2005;Peretti et al 2006;Wo´jcik et al 2011Wo´jcik et al , 2013Wo´jcik et al , 2014Wo´jcik and Smalec 2012a). The present authors also did not observe significant differences in the mean number of SCEs between chinchillas of different sexes.…”
Section: Discussioncontrasting
confidence: 80%
“…Age significantly affects the incidence of SCE. Older animals develop more SCEs per cell compared with younger animals (Sinha et al 1985;Lazutka et al 1994;Peretti et al 2006;Husum et al 2008;Wnuk et al 2011;Wo´jcik et al 2011), and differences in the numbers of SCEs between old and young chinchillas were also observed in the present study. We observed a highly interesting interrelationship.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…For a more complete assessment of somatic mutagenesis of mesenchymal stem cells, a micronucleus test was performed. The formation of cells with micronuclei is the result of chromosomal ruptures or defects in the mitotic spindle, which is consistent with the manifestation of aneuploidy (15,18,19,(22)(23). The normal frequency of cells with micronuclei in mammals is 1.6‰-5.6‰ (8).…”
Section: Discussionsupporting
confidence: 53%